2009
DOI: 10.1242/jcs.043216
|View full text |Cite
|
Sign up to set email alerts
|

Copper transport into the secretory pathway is regulated by oxygen in macrophages

Abstract: Copper is an essential nutrient for a variety of biochemical processes; however, the redox properties of copper also make it potentially toxic in the free form. Consequently, the uptake and intracellular distribution of this metal is strictly regulated. This raises the issue of whether specific pathophysiological conditions can promote adaptive changes in intracellular copper distribution. In this study, we demonstrate that oxygen limitation promotes a series of striking alterations in copper homeostasis in RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 47 publications
7
95
0
Order By: Relevance
“…The finding that hypoxia induces Cu transport into macrophages and, thereby, increases their bactericidal potential (7,16) and the fact that hypoxia does not exist in Mtb-infected mice (17) indicate that mice might not be a good animal model to examine the role of MctB in virulence of Mtb. By contrast, in guinea pigs, Mtb induces formation of discrete, granulomatous lesions with central necrosis and dystrophic mineralization similar to those of humans.…”
Section: Manuscript Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that hypoxia induces Cu transport into macrophages and, thereby, increases their bactericidal potential (7,16) and the fact that hypoxia does not exist in Mtb-infected mice (17) indicate that mice might not be a good animal model to examine the role of MctB in virulence of Mtb. By contrast, in guinea pigs, Mtb induces formation of discrete, granulomatous lesions with central necrosis and dystrophic mineralization similar to those of humans.…”
Section: Manuscript Textmentioning
confidence: 99%
“…By contrast, in guinea pigs, Mtb induces formation of discrete, granulomatous lesions with central necrosis and dystrophic mineralization similar to those of humans. We considered formation of these hypoxic granulomas as important for assessing the role of Cu in the mammalian immune system, because oxygen limitation was shown to stimulate Cu delivery to phagosomes containing bacteria (16). To examine the role of Cu in the response of guinea pigs to infection with Mtb, we isolated, microdissected and pooled granulomas from lungs of guinea pigs infected with WT Mtb H37Rv and analyzed trace minerals by flame atomic absorption spectrophotometry as described (18).…”
Section: Manuscript Textmentioning
confidence: 99%
“…Consistent with this notion, a previous study found that macrophages increase copper uptake and deliver the available copper into phagosomes under hypoxic conditions [42]. The interplay of the complex signals from various stress conditions (hypoxia, nutrient deprivation, exposure to heavy metals) may ultimately define the in vivo host environment in which M. tb establishes the latent infection.…”
Section: Discussionmentioning
confidence: 53%
“…Copper transport in macrophages is regulated in an oxygen-dependent manner. Hypoxia induces ATP7A protein expression and trafficking of ATP7A from the TGN to post-Golgi vesicles in a copper-dependent manner [84]. Furthermore, hCTR1 protein expression and copper uptake are induced by hypoxia.…”
Section: Posttranslational Regulation Of Copper Transportmentioning
confidence: 99%
“…Furthermore, hCTR1 protein expression and copper uptake are induced by hypoxia. During hypoxia, copper delivery to Cu/Zn dismutase (SOD1) and to COX1, a subunit of cytochrome c oxidase, is inhibited, whereas more copper is incorporated into ceruloplasmin in the secretory pathway by ATP7A [84]. Apparently, hypoxia results in an increased copper uptake and a redistribution of copper to different compartments in the cell to adapt to cellular need.…”
Section: Posttranslational Regulation Of Copper Transportmentioning
confidence: 99%